17D yellow fever vaccine elicits comparable long-term immune responses in healthy individuals and immune-compromised patients. Issue 6 (June 2016) - Wieten, R.W.; Goorhuis, A.; Jonker, E.F.F.; de Bree, G.J.; de Visser, A.W.; van Genderen, P.J.J.; Remmerswaal, E.B.M.; ten Berge, I.J.M.; Visser, L.G.; Grobusch, M.P.; van Leeuwen, E.M.M.
Summary: Background: The 17D live attenuated yellow fever (YF) vaccine is contra-indicated in immune-compromised individuals and may elicit a suboptimal immunologic response. The aim of this study is to assess whether long-term immune responses against the YF vaccine are impaired in immune-compromised patients. Materials and methods: Fifteen patients using different immunosuppressive drugs and 30 healthy individuals vaccinated 0–22 years ago were included. The serological response was measured using the plaque reduction neutralization test (PRNT). CD8 + and CD4 + T-cell responses were measured following proliferation and re-stimulation with YFV peptide pools. Phenotypic characteristics and cytokine responses of CD8 + T-cells were determined using class I tetramers. Results: The geometric mean titre of neutralizing antibodies was not different between the groups (p = 0.77). The presence of YFV-specific CD4 + and CD8 + T-cell did not differ between patients and healthy individuals (15/15, 100.0% vs. 29/30, 96.7%, p = 0.475). Time since vaccination correlated negatively with the number of YFV-specific CD8 + T-cells (r = −0.66, p = 0.0045). Percentages of early-differentiated memory cells increased (r = 0.67, p = 0.017) over time. Conclusion: These results imply that YF vaccination is effective despite certain immunosuppressive drug regimens. An early-differentiated memory-like phenotype persisted, which is associated with effective expansion upon re-encounter with antigen, suggesting a potent memory T-cell pool remains.